Practical Guide on the Potential of Capital Markets Development in Small Economies - World Bank Group (World Bank, Washington, DC, 2019)
The World Bank, with support from authorities in the Western Balkans, has developed a practical guide for capital markets development in small economies. The guide supports the implementation of the Multi-Annual Action Plan for a Regional Economic Area in the Western Balkans Six by helping inform policy discussions around capital markets development, including to what extent capital markets have potential and should be given priority in the region and small economies more broadly. The practical guide aims to provide regulators and policymakers in small economies with an overview of the capital market development agenda and existing challenges. The guide aims to support policymakers and regulators of small economies identify general preconditions, key constraints, and areas of potential for development of local capital markets. A framework for analysis of preconditions and capital markets development has been developed to guide reforms in small economies. A pilot of the methodology in Serbia helped further advance the framework and adapt it to the realities that small economies face. The framework for analysis of the preconditions and capital markets is outlined in Annex two. The practical guide focuses on both necessary preconditions and on relevant specific issues in capital markets development. It includes an assessment of the macro-fundamental preconditions that need to be in place to make capital markets development possible, including macro-political stability, level of savings, the structure of corporate sector, the broader legal and regulatory framework (including insolvency law and tax law), the level of real interest rates, and the soundness of the banking sector.